The Republic of Moldova as a Potential Failing State? - Dominika Kosárová; Jaroslav Ušiak (Vasyl Stefanyk Precarpathian National University, 2017)
The Republic of Moldova is a young post-Soviet country facing a continuous internal struggle in the definition of its identity given its location between two major geopolitical blocs - Euroatlantic and Eurasian. In consequence to the combination of several internal and external factors it has striven to stabilize its political scene, sustain economic growth and enhance defense capabilities since its creation. Yet the success is questionable and Moldova today manifests certain features of state fragility. The aim of the article is to answer the question whether Moldova can be regarded as a failing state and if so, which areas in terms of sectoral security are stricken the most by state fragility. The authors point to the shortcomings that Moldova exhibits in political, economic and military sectors of security and concludes that potential failure of Moldova may have serious geopolitical consequences given the interests of external actors, especially Russia. The authors also suggest that the future development of Moldova will depend to a large extent on the attitude and role of the European Union in regard to the stabilization of the state.